Survival strategies of Rhinocladiella similis in perchlorate-rich Mars like environments - Alef dos Santos; Júnia Schultz; Felipe Oliveira Souza; Lucas Rodrigues Ribeiro; Thiago Verano Braga; Eduardo Jorge Pilau; Edson Rodrigues-Filho; Alexandre Soares Rosado (npj Microgravity)
Abstract Studying the survival of terrestrial microorganisms under Martian conditions, particularly in the presence of perchlorates, provides crucial insights for astrobiology. This research investigates the resilience of the extremophile black fungus Rhinocladiella similis to magnesium perchlorate and UV-C radiation. Results show R. similis, known for its tolerance to acidic conditions, exhibits remarkable resistance to UV-C radiation combined with perchlorate, as well as to high concentrations of magnesium perchlorate, surpassing Exophiala sp. strain 15Lv1, a eukaryotic model organism for Mars-like conditions. Growth curve analyses revealed both strains can thrive in perchlorate concentrations mimicking Martian perchlorate-rich environments, with R. similis adapting better to higher concentrations. Morphological and protein production changes were investigated, and mass spectrometry identified perchlorate-induced proteins, advancing molecular understanding of potential microbial life on Mars. These findings advance knowledge of extremophile capabilities, contributing to the search for life beyond Earth and informing the design of future Martian rovers equipped for biosignature detection.